Discrepancy between RFR and FFR based decision on revascularization – is coronary microcirculatory dysfunction responsible?. (25th November 2020) - Niewiara, L; Guzik, B; Szolc, P; Zmudka, K; Legutko, J
Abstract: Introduction: Confirmation of significant ischemia is crucial for proper management of coronary artery disease. Non-hypaeremic indices along with fractional flow reserve are endorsed by current guidelines to prove ischemia. However some discrepancies between hyperaemic and non-hyperaemic decision on revascularisation is present in significant percentage of cases. Aim: Aim of our study was to determine frequency of coronary microcirculatory dysfunction in patients with discrepant RFR and FFR measurements compared to concordant group. Methods: Resting full cycle ratio (RFR) was measured in 69 left anterior descending arteries, all patients had symptoms of chronic coronary syndromes (CCS II-III). Cut-off values for ischemia detection were ≤0.80 for FFR and ≤0.89 for RFR. Coronary microcirculatory dysfunction (CMD) was defined as CFR <2.0 or IMR ≥25 according to current guideline. Results: Discrepancy between FFR and RFR decision on revascularisation was present in 18 (26.1%) of cases. Mean age of patients was 65 (SD=8.5), all patients were similar in terms of diabetes, prior MI or hypertension and statin use (p=NS for all comparisons). Group with discordant RFR and FFR results had higher prevalence of CMD compared to patients with concordant result (44.4% vs 21.6% respectively, p=0.004), however median values of CFR and IMR were similar (see table). Conclusions: Patients with discrepant results have more frequently coronary microcirculatory dysfunction. Coronary microcirculatory dysfunction should be further investigated as it could explain discrepancies between RFR and FFR based decision on revascularisation. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): Jagiellonian University statutory grant